(untitled) (The International Journal for Scientific Research, 2026)
This research examines the official mortgage (al-Rahn al-Rasmi) as the most powerful form of in-kind guarantee within the framework of the Saudi Civil Transactions System, issued by Royal Decree No. (M/191) of 1443 AH. The significance of this study stems from the pivotal role played by the official mortgage in securing credit and facilitating financing in the Kingdom of Saudi Arabia. The research adopts an analytical-deductive methodology in analyzing the regulatory texts, supported by an applied approach. It is structured into three main sections: the first addresses the nature of guarantees and the place of the official mortgage among them; the second examines the conditions for the formation of the official mortgage and its effects; and the third covers the enforcement of the mortgage, debt satisfaction, and established legal principles. The research concludes that the official mortgage is a formal accessory contract that is not enforceable against third parties except through registration, and that the mortgagee has no right to directly possess the mortgaged property but must satisfy his right through a public auction sale under the Enforcement System. This balance protects the creditor’s rights while safeguarding those of the debtor and other creditors. The research recommends simplifying registration procedures electronically and publishing guiding judicial principles in mortgage and enforcement disputes.